Penerapan PSAK 107 Atas Pembiayaan Ijarah Multijasa Pada BMT AL-Fath IKMI Cabang Legoso - Angga Abdur Rokhim; Rizky Maulana Pribadi (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2020)
The purpose of this study is to analyze the application of multi-service Ijarah transactions in BMT Al-Fath IKMI Legoso branch for their compliance with PSAK 107. The urgency of the suitability of accounting application with PSAK is considered important because it is one of the causes of a healthy economic climate and blessings for all. The method used is descriptive qualitative method. The results showed that BMT Al-Fath IKMI Legoso branch has not been fully compliant in applying multi-service Ijarah accounting in accordance with PSAK 107. The suitability indicators start from the definition of Ijarah, Ijarah characteristics, accounting recognition & measurement as owner, recognition & measurement of accounting as tenant, further Ijarah, presentation, until proficiency. All of the indicators are in accordance with PSAK 107 except for BMT products of the Advanced Ijarah type in accounting records as the lessee does not recognize and measure the Cost of Maintenance of ijarah objects. Then BMT in accounting records as a leasing agent does not recognize and measure the Cost of Repairing ijarah objects. The data collection method in this study is to use primary data which includes interviews, observations, and documentation.